Slowing of Electrical Activity in Ventricular Fibrillation is Not Associated with Increased Defibrillation Energies in the Isolated Rabbit Heart - Caldwell, Jane; Burton, Francis; Cobbe, Stuart; Smith, Godfrey (Frontiers in Physiology, 2011)
Prolonged out-of-hospital ventricular fibrillation (VF) arrests are associated with reduced ECG dominant frequency (DF) and diminished defibrillation success. Partial reversal of ischaemia increases ECG DF and improves defibrillation outcome. We have investigated the metabolic components of ischaemia responsible for the decline in ECG DF and defibrillation success. Isolated Langendorff-perfused rabbit hearts were loaded with the voltage-sensitive dye RH237. Using a photodiode array, epicardial membrane potentials were recorded at 252 sites (15x15mm) on the anterior surface of the left & right ventricles. Simultaneously, a global ECG was recorded. VF was induced by burst pacing, and after 60s, perfusion was either reduced to 6ml/min or the perfusate composition changed to impose hypoxia (95%N2/5%CO2), pH 6.7 (80%O2/20%CO2), or hyperkalaemia (8mM). Using Fast Fourier Transform, power spectra were created from the optical signals and the global ECG. The optical power spectra were summated to give a global power spectrum (pseudoECG). At 600s the minimum defibrillation voltage (MDV) was determined by step-up protocol. During VF, the ECG and pseudoECG DF were reduced by low-flow ischaemia (9.0±1.0Hz, p<0.01, n=5) and raised [K+]o (12.2±1.3 Hz, p<0.05, n=7) compared to control (19.2±1.5 Hz, n=20), but were unaffected by acidic pHo (16.7±1.1 Hz, n=11) and hypoxia (14.0±1.2 Hz, n=10). In contrast, the MDV was raised by acidic pH (156.1±26.4V, p<0.001) and hypoxia (154.1±22.1V, p<0.01) compared to control (65.6±2.3V), but comparable changes were not observed in low-flow ischaemia (61.0±0.5V) or raised [K+]o (56±3V). In summary, different metabolites are responsible for the reduction in DF and the increase in defibrillation energy during ischaemic VF.